Recontextualização no ensino remoto: covid-19, docência e vulnerabilidade - Maxsuel Vieira Batista (2023)
Teachers in Brazil and around the world had their lives and professional practices impacted by the covid-19 pandemic. In Minas Gerais, face-to-face classes were suspended on March 17, 2020, and on May 18, 2020, remote activities began under the “Special Regime for Non-On-Campus Activities” (REANP), basically based on three pillars: the “Tutored Study Plan” (PET), the television program “Connect with Education”, and the digital “Connection School” application. This study aims to understand the role of teachers in the processes of recontextualization of the officially proposed curricular policy, and the construction/use of pedagogical discourse, during the period of the covid-19 pandemic, for students in social vulnerability, in the context of the implementation and execution of remote teaching in the state public education network of Minas Gerais. Of a qualitative nature, data collection was carried out through partially structured interviews. Data analysis involved document analyzed from the perspective of Critical Discourse Analysis. It is hoped that this study can contribute to the understanding of the recontextualization process, to subsidize the proposition of improvements in curricular public policies. And that broadens the understanding of the difficulties faced by basic education teachers, in emergency moments of non-face-to-face activities, especially in schools where social vulnerability was enhanced by the covid-19 pandemic, to think about actions hat mitigate the negative impacts of this period of health emergency.